EDUKASI SEKSUAL DENGAN MEDIA KARTU BERSERI BAGI SISWA SD NEGERI 36 GUNUNG SARIK KOTA PADANG - Ahmad Hidayat; Nadia Chalida Nur; Elsi Novnariza (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The high rate of violence, abuse and sexual perversion among children in Indonesia is increasingly worrying. Sexual education has not yet been included in the academic curriculum in primary or secondary schools in Indonesia. Sexual education is still thematic and given when meeting the right moment that is not planned. The purpose of this activity is to increase knowledge about sexual problem prevention behavior for children using serial card education media. The activity was carried out at SDN 36 Gunung Sarik Padang, for 54 grade 6 students. The method of this activity was divided into several stages, namely brainstorming with the school principal, developing serial card education media, disseminating serial card media to schools, and sexual education using serial card media. to students. The paired data hypothesis analysis results obtained from the pre-test and post-test for students showed that sexual education using serial card media was effective in increasing students' knowledge of preventive behavior from various risks of violence, harassment, and sexual perversion. Continuous efforts are needed in shaping positive behaviors to prevent sexual problems in children, with the involvement of various parties, such as parents, teachers and peers, as well as policies from upstream in the form of the provision of an academic curriculum.